Relationship of occupational health and safety training with health literacy among employees working in the various lines of business - Sevinc, Nergiz; Korkut, Burcu (Faculty of Medicine, Universitas Trisakti, 2020)
BackgroundHealth literacy is vital for people’s ability to manage health. It has been known for a long time that the importance of education in increasing health literacy is an undeniable fact. The first aim of this study was to investigate the health literacy levels of employees working in different business lines receiving service from the occupational health and safety unit. The second aim was to reveal how health literacy levels are affected according to the training duration.MethodsA cross-sectional study was conducted on 202 employees receiving service from the Karabuk occupational health and safety unit. The employees were divided into three groups as workers, officers and others. All employees were given the questionnaire consisting of 31 questions including sociodemographic characteristics and the adult health literacy scale. A face-to-face interview was performed with each of the employees. Kruskal-Wallis H and Mann-Whitney U tests were used to analyze the data.ResultsThe range of adult health literacy scale scores of the employees was 4-23. There was no significant difference in adult health literacy scale scores between age groups (p=0.38). The percentage of employees who received more than 16 hours training course was 19.3%, 20.6%, and 46.7% for workers, civil servants and other employees, respectively. Adult health literacy scale scores increased in proportion to the amount of training the employees received (p=0.001).ConclusionThis study reveals that occupational health training has a positive effect on health literacy.